Chloroplast genome evolution in Passiflora - Santos, Luiz Augusto Cauz dos (2020)
Chloroplast genomes (cpDNAs or plastomes) are highly conserved in Angiosperms. Although rearrangements have been observed in some lineages, the mechanisms that lead to rearrangements are still poorly elucidated. Our research group initially reported the structural organization of the plastome of Passiflora edulis (Passifloraceae) and rearrangments were identified. It is particularly worth noting that Passiflora presents different patterns of chloroplast inheritance and cytonuclear incompatibility. In order to investigate cpDNA evolutionary history in Passiflora and its possible implications for infrageneric taxonomic classification, a total of 35 complete chloroplast genomes were obtained, sampling for species of subgenera Astrophea, Decaloba, Deidamioides and Passiflora. The organization of the cpDNAs was uncommon, with large variation in size (~60 kb between shortest and longest), and highly rearranged genome structures. In addition, although large inverted repeat (IR) expansions were identified, the exact opposite (loss of an IR) was detected for the first time in Passiflora. This is indeed a rare event in angiosperms. A repertory of rearrangements, such as inversions and losses of genes was also found, making Passiflora one of the few groups with complex chloroplast genome evolution. Interestingly, a high number of rearrangements was detected in subgenus Decaloba, in which biparental chloroplast inheritance occur. A comparative genomic analysis revealed different organizational plastome structures, in accordance with the taxonomic classification within the subgenus Deidamioides. In addition, the plastid phylogenomics resulted in a highly supported tree with polyphyletic placement of Deidamioides species. Based on the combined results, we suggest elevating the status of the section Tryphostematoides (Deidamioides) to subgenus Tryphostematoides. Finally, apart from the contribution of this work to elucidating evolutionary history of Passiflora, our results also show that Passiflora provides a good model for the study of chloroplast genome evolution.